Geografias do acontecer: as táticas espaciais de mobilização do(s) movimento(s) LGBT+ em Ponta Grossa – Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This thesis aims to investigate how the spatial tactics of the LGBT+ movement in Ponta Grossa, Paraná, are constituted through the integration of research and activism, combining the ethnogeographic perspective with non-representational theories. Considering the relevance of daily life and performances in space as central dimensions of Geography, the research sought to understand the temporal and spatial dynamics that shape the actions of the LGBT+ movement. Aligned with non-representational theories in Geography (Anderson & Harrison, 2010) and the relational and multidimensional conception of space (Massey, 2008), the study addressed the following specific questions: (i) What are the material and immaterial elements that constitute the practices of the LGBT+ movement in Ponta Grossa? (ii) How are the spatial tactics of this movement carried out in terms of production, maintenance, and transformation of space? (iii) How does temporality influence these tactics? The research adopted an autoethnographic approach (Heidrich, 2016; Costa, 2016), grounded in participant observation and the creation of field diaries, conducted within four key groups of the LGBT+ movement in Ponta Grossa: Associação Flor de Lis LGBT, Fórum Municipal dos Direitos LGBT+, Parada Cultural LGBTQIA+, and Comissão de Diversidade Sexual e de Gênero da OAB-Ponta Grossa. For interpretations, theoretical perspectives emphasizing processuality and relationality were incorporated, employing concepts such as performativity (Butler, 2003) and the inseparability of space and time, considering space as co-produced by embodied practices, materialities, and affects in constant flux and transformation. The proposed interpretation highlights that the LGBT+ movement in Ponta Grossa operates across multiple scales and temporalities, articulating tactics ranging from large public events, such as demonstrations and parades, to seemingly ephemeral everyday practices, such as informal gatherings, virtual mobilizations, and social media posts. These actions underline the dynamic and processual nature of the movement, whose political strength lies in its ability to delineate spaces of resistance and contestation. The analyses also suggest that the movement operates through provisional, ephemeral, and fluid arrangements, reflecting the complexity and heterogeneity of the group while facing challenges imposed by hegemonic normative structures. From a non- representational perspective, the focus was on events, movement, and lived experience, allowing the understanding of practices as emerging phenomena. Through field immersions, it became evident that the LGBT+ movement in Ponta Grossa operates via tactics ranging from large public mobilizations and institutional actions to seemingly mundane everyday interactions, such as café meetings and virtual mobilizations. These practices demonstrate a dynamic and processual character, highlighting the movement’s ability to resist and adapt in the face of hegemonic structures that seek to restrict plurality and diversity. Furthermore, the movement is marked by creative actions that re-signify both public and private spaces, challenging hegemonic norms and advocating for new political and cultural configurations. The thesis concludes that the spatial tactics of the LGBT+ movement in Ponta Grossa are creative and relational actions, simultaneously operating across multiple scales and temporalities, emphasizing the importance of understanding space as a performative and relational dimension where bodies, meanings, and materialities intertwine to contest hegemonies and foster resistances.
Keywords: Espaço Geográfico; Movimento LGBT+; Teorias não-representacionais; Geografias do acontecer; Ponta Grossa; Geografia